Masculinity, race and national identity: representations of non-Japanese men’s speech in contemporary Japanese novels - Suzuki, Satoko (Gender and Language, 2020)
Language ideologies have been of central concern to the study of Japanese language, gender and society. Many scholars have researched ideologies surrounding representations of Japanese women’s speech; however, investigations of representations of men’s speech have been limited. This study contributes to filling this gap through the analysis of non-Japanese male characters found in contemporary Japanese novels. The article reveals that authors assign strongly masculine expressions to their East Asian characters much more frequently than to their white characters and argues that these differentiated representations of non-Japanese male characters’ speech reproduce and are influenced by ideologies concerning cultural nationalism, racial determinism, class and sexuality. Linguistic data are presented that both unsettle the constructed image of Asian males as asexual beings and question the historically assumed relationship between gendered language and authenticity.
Keywords: arts; asie; cours; discipline; histoire et politique; japon; lin2685; linguistique; masculinité; premier cycle; représentation des hommes; régions géographiques; sciences humaines; sofia; thématiques; études littéraires

S’approprier son genre entre pathologie et résistance. La transidentité après la Révolution islamique en Iran - Azadi, Bahar (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2020)
Keywords: asie; corps; cours; fem3400; identités LGBTQIA2+; iran; islam; personnes trans*; premier cycle; ressource en ligne; régions géographiques; thématiques

Hindu nation and its queers: Caste, islamophobia, and de/coloniality in India - Upadhyay, Nishant (Interventions: international journal of postcolonial studies, 2020)
Le jugement de la Cour suprême indienne de 2018 dépénalisant l'homosexualité a été qualifié d'"acte décolonial". Article 377, qui criminalisait l'homosexualité, était une loi coloniale introduite par les Britanniques en Inde, que l'État postcolonial a maintenue jusqu'en 2018. Le jugement peut être « décolonial » dans son intention, mais il y a d'autres processus simultanés en jeu qui ne sont pas si décoloniaux dans la pratique ; cet essai soutient que ces processus sont le colonialisme, la suprématie brahmanique et l'islamophobie. La violence basée sur la caste fait partie intégrante de l'hindouisme et est étroitement liée à d'autres matrices d'oppression, faisant de la caste le fondement de toute revendication de l'hindouisme en tant que queer, trans et non conforme au genre amical. Étudiant les récentes réponses nationalistes hindoues en faveur de la dépénalisation de l'homosexualité en Inde, cet essai retrace comment la droite hindoue déploie la queerness pour propager ses agendas islamophobes, castistes et homohindunationalistes. L'essai défend la décolonisation du droit, de l'État.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cours; discours dominant; fem3400; inde; islamophobie; premier cycle; périodes historiques; queer; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; violences